Financial Sector Reform in Jamaica During 1985-1992, Possible Lessons for the Caribbean - Marston, Dewitt (IMF Working Papers; Working Paper ;, 1995)
This paper reviews the Jamaican experience with indirect instruments and contrasts this with the currency board type arrangements of the common currency area governed by the Eastern Caribbean Central Bank (ECCB). Reforms in Jamaica improved intermediation and banking efficiency, but a weak fiscal position and interest rate caps undermined the effectiveness of indirect instruments in attaining monetary control. The apparent stability amongst members of the currency union may mask fiscal pressures. In most Caribbean countries, problems of quasi-fiscal pressures on money supply, and disintermediation due to some regulation, are evident. Resolving these issues are necessary to facilitate the reforms being pursued.